Analisis Jalur Evakuasi Tsunami untuk Pengunjung di Pesisir Klayar, Kabupaten Pacitan - Shilna Kayfiyata Shohiyha; Dewi Novita Sari; Danardono; Jumadi (Mataram University, 2026)
This study aims to determine strategic evacuation locations and optimal evacuation routes for visitors in the Klayar Coast area, Pacitan Regency, based on tsunami modeling scenarios with wave heights of 8.5 meters and 20 meters. This region has a high level of tsunami vulnerability due to its direct exposure to the Indian Ocean and its location within a zone of regional tectonic activity, while the intensity of tourism activities has led to a significant increase in the number of people exposed to risk. The study applies tsunami hazard zone modeling based on topographic and elevation data, combined with evacuation route network analysis using a Geographic Information System (GIS). Evacuation travel time was calculated by considering route length, topographic conditions, and average evacuation speed under emergency conditions. The results show that the 20-meter tsunami scenario causes a significant expansion of high-hazard zones and increases evacuation travel time by approximately 3.5–6 minutes compared to the 8.5-meter scenario. Several evacuation routes and Temporary Evacuation Sites (TES) that are effective under the lower scenario become suboptimal under the higher scenario. The novelty of this study lies in the integration of travel-time-based evacuation route analysis with multi-scenario tsunami modeling in a coastal tourism area, providing a more adaptive spatial basis for tsunami mitigation planning. These findings emphasize the importance of worst-case-scenario-based evacuation planning and the strengthening of early warning systems to enhance visitor safety.